Using Attribution Theory To Explain The Affective Dispositions Of Tireless Moral Monitors Toward Narrative Characters. (1st October 2018) - Tamborini, Ron; Grall, Clare; Prabhu, Sujay; Hofer, Matthias; Novotny, Eric; Hahn, Lindsay; Klebig, Brian; Kryston, Kevin; Baldwin, Joshua; Aley, Melinda; Sethi, Neha
Abstract: Recent literature suggests that affective disposition theory (ADT) has difficulty explaining the appeal of protagonists that sometimes do bad things. We addressed this issue by integrating logic from attribution theory with ADT. Three studies examined whether causal factors identified in attribution theory's covariation model (consensus, distinctiveness, and consistency) affected internal/external attributions (for a character's harmful behavior) to shape liking for characters seen inflicting extreme harm. In Study 1, a 2 × 2 × 2 experiment varied (high vs low) the perceptions of consensus, distinctiveness, and consistency associated with a protagonist's harmful acts to examine their effect on liking for a well-known hero. In a 3 × 2 × 2 × 2 experiment using an unknown character, Studies 2 and 3 added to Study 1's design by varying character type (imperfect hero, morally equivocal character, villain). Findings indicate narrative cues serve as antecedent factors that prompt either internal or external attributions for a protagonist's harmful behavior. Internal attributions negatively predict character liking, whereas external attributions are positive predictors. Findings suggest that writers, when they want viewers to like characters, may use attribution theory principles to signal that external factors caused the character's harmful acts. We discuss this belief as an alternative to models that explain the appeal of protagonists who behave immorally, reasoning that initially-activated character schema can bias audiences in favor of a protagonist and minimize the importance of moral judgment.